PENGEMBANGAN POLA AFEKTIF DALAM PEMBELAJARAN BERBASIS TEKNOLOGI: PENELITIAN METODE CAMPURAN PADA SEKOLAH DASAR DI INDONESIA. - Afriani, Rita; Jasrial; Zen, Zelhendri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the development of students’ affective patterns in technology-based learning at the elementary school level in Indonesia. The main focus is to analyze how the integration of technology in the learning process influences students’ affective aspects, including motivation, learning interest, engagement, and attitudes toward classroom activities. The research employed a mixed-methods approach with a sequential explanatory design, in which quantitative data collection was followed by qualitative data to strengthen the findings. Quantitative data were gathered through questionnaires distributed to elementary school students, while qualitative data were obtained through teacher interviews and classroom observations. The findings indicate that the use of technology in learning contributes positively to the development of students’ affective patterns. Students become more motivated, more actively engaged in learning activities, and demonstrate more positive attitudes toward the learning materials. However, the effectiveness of technology-based learning is still influenced by several factors, such as teachers’ readiness to implement technology, the availability of infrastructure, and the design of instructional activities. In conclusion, technology-based learning has significant potential to enhance students’ affective domain in elementary education, provided that it is supported by appropriate and sustainable implementation strategies.